Deep Phenotyping and Genetic Characterization of a Cohort of 70 Individuals With 5p Minus Syndrome - Nevado, Julián; Bel-Fenellós, Cristina; Sandoval-Talamantes, Ana Karen; Hernández, Adolfo; Biencinto-López, Chantal; Martínez-Fernández, María Luisa; Barrúz, Pilar; Santos-Simarro, Fernando; Mori-Álvarez, María Ángeles; Mansilla, Elena; García-Santiago, Fé Amalia; Valcorba, Isabel; et al. (Frontiers in Genetics, 2021)
RACT Chromosome-5p minus syndrome (5p-Sd, OMIM #123450) formerly known as Cri du Chat syndrome results from the loss of genetic material at the distal region of the short arm of chromosome 5. It is a neurodevelopmental disorder of genetic cause. So far, about 400 cases have been reported worldwide. Individuals affected by this syndrome have large phenotypic heterogeneity. However, a specific phenotype has emerged including global developmental delay, microcephaly, delayed speech, some dysmorphic features, and a characteristic and monochromatic high-pitch voice, resembling a cat´s cry. We here describe a cohort of 70 patients with clinical features of 5p- Sd characterized by means of deep phenotyping, SNP-arrays, and other genetic approaches. Individuals have a great clinical and molecular heterogeneity, which can be partially explained by the existence of additional significant genomic rearrangements in around 39% of cases. Thus, our data showed significant statistical differences between subpopulations (simple 5p deletions versus 5p deletions plus additional rearrangements) of the cohort. We also determined significant “functional” differences between male and female individuals.